Factors related to any-breastfeeding duration in a sample of Malay mothers - M., Siti Farhana; Omar, Noraida; Sulaiman, Norhasmah; Mohd Yusof, Barakatun Nisak (Community Health Society Malaysia, 2017)
Background: While the benefits of breastfeeding have been established, sustaining breastfeeding for a longer duration is a challenge. This cross-sectional study aimed to determine factors related to any breastfeeding duration in a sample of the ever-breastfed Malay mothers. Materials and Methods: Mothers regardless of their current breastfeeding status and having a child between 12 and 36 months participated in this study. We assessed breastfeeding practices, obstetric history, nutritional status and information about their breastfed child. Results: A total of 60 ever-breastfed mothers aged 30.9 + 3.4 years participated in the study. The duration of any breastfeeding was 15.0 ± 7.6 months with 31.7% were still breastfed up to 24 months. The BMI of the participants was in the normal range but increased by 1.8kgm-2 as compared to the pre-pregnancy BMI. Intake of macronutrients distributed evenly but a substantial proportion of the participants did not achieve the recommendations for energy, calcium and iron intake. Mother’s age (r = 0.288, p < 0.05), duration of exclusive breastfeeding (r = 0.408, p < 0.01) and later introduction to formula milk (r= 0.550, p < 0.001) were positively related with duration of any breastfeeding. Conclusion: In this sample of ever breastfed Malay women, only 31.7% were still breastfeeding. The increase in BMI at a postpartum and possible micronutrients inadequacy are of a particular concern. A longer duration of any breastfeeding was related to a longer duration of exclusive breastfeeding, the mother’s age and later introduction to formula-feeding. Understanding issues of breastfeeding mothers help to sustain a longer duration of breastfeeding.